Effects of electron beam radiation dose on the compatibilization behaviour in recycled polypropylene/microcrystalline cellulose composites - Samat, Noorasikin; Motsidi, Siti Nor Rasyidah; Mohd Lazim, Nurul Hakimah (IOP Publishing, 2018)
The purpose of this research was to evaluate the influence of dose level of electron beam on the compatibilization behavior of recycled polypropylene (rPP) in rPP/microcrystalline cellulose (MCC) composites. Initially, the rPP was irradiated with various dose of electron beam (5 kGy up to 250 kGy) which then mixed with unirradiated rPP (u-rPP) at a ratio of 30:70 respectively. The composites were prepared by incorporating a series wt% of MCC fibers into rPP (u-rPP : i-rPP) using extruder and finally moulded with an injection moulding machine. The compatibility behavior of irradiated rPP (i-rPP) were analysed with mechanical tensile and thermal methods. The results of mechanical analysis showed great improvement in tensile modulus but an increase in radiation dosage gradually decreased this property. Nevertheless, the tensile strength exhibited a minor effect. The thermal stability of composites is lowered with increase in the absorbed dose, more significantly at higher content of MCC. Fracture surface observations reveal adhesion between the cellulose and rPP matrix